Black Liberation research: qualitative methodological considerations. Issue 9 (21st October 2019) - Stewart, Saran; Haynes, Chayla
Abstract: This article provides an overview of critical qualitative considerations for Black Liberation Research. The methodological considerations focus on: (a) resistance research as paradigm, (b) researcher positionality, (c) naming Black deprivation as the problem of study, (d) situating Black Liberation as the aim of analysis, and (e) centering emotions as humanizing methods. Taken together, the articles in this special issue provide an example of how Black Liberation Research can support the #BLM movement and simultaneously seek to disrupt Black deprivation in the academy.